Global Significant Changes in Formaldehyde (HCHO) Columns Observed From Space at the Early Stage of the COVID‐19 Pandemic. Issue 4 (23rd February 2021) - Sun, Wenfu; Zhu, Lei; De Smedt, Isabelle; Bai, Bin; Pu, Dongchuan; Chen, Yuyang; Shu, Lei; Wang, Dakang; Fu, Tzung‐May; Wang, Xiaofei; Yang, Xin
Abstract: Satellite HCHO data are widely used as a reliable proxy of non‐methane volatile organic compounds (NMVOCs) to constrain underlying emissions and chemistry. Here, we examine global significant changes in HCHO columns at the early stage of the COVID‐19 pandemic (January–April 2020) compared with the same period in 2019 with observations from the TROPOspheric Monitoring Instrument (TROPOMI). HCHO columns decline (11.0%) in the Northern China Plain (NCP) because of a combination of meteorological impacts, lower HCHO yields as NO x emission plunges (by 36.0%), and reduced NMVOC emissions (by 15.0%) resulting from the lockdown. HCHO columns change near Beijing (+8.4%) due mainly to elevated hydroxyl radical as NO x emission decreases in a NO x ‐saturated regime. HCHO columns change in Australia (+17.5%), Northeastern Myanmar of Southeast Asia (+14.9%), Central Africa (+7.8%), and Central America (+18.9%), consistent with fire activities. Our work also points to other changes related to temperature and meteorological variations. Plain Language Summary: We use satellite observations to examine global significant changes in HCHO columns at the early stage of the COVID‐19 pandemic compared with the same period in 2019. HCHO columns decreased in the Northern China Plain caused by a joint effect of meteorology, reduced anthropogenic NO x, and decreased non‐methane volatile organic compound emissions during the lockdown. The impact of temperature and meteorology on HCHO columns is observed in Northwestern China, India, Southern Africa, Eastern Brazil, Southern Cone, and Northeastern Thailand of Southeast Asia. Regional changes in Southeastern Australia, Northeastern Myanmar of Southeast Asia, Central Africa, and Central America are likely driven by open fire activities. Key Points: We detect significant changes in HCHO columns worldwide at the early stage of the COVID‐19 pandemic We see evidence of changing atmospheric oxidizing capacity and NMVOC emissions in the Northern China Plain due to the massive lockdown Besides anthropogenic emission, temperature and open fires are vital factors dominating variations in HCHO columns